2020
DOI: 10.1186/s12936-020-03190-z
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of statistical methods for safety data in malaria chemoprevention in pregnancy trials

Abstract: Background: Drug safety assessments in clinical trials present unique analytical challenges. Some of these include adjusting for individual follow-up time, repeated measurements of multiple outcomes and missing data among others. Furthermore, pre-specifying appropriate analysis becomes difficult as some safety endpoints are unexpected. Although existing guidelines such as CONSORT encourage thorough reporting of adverse events (AEs) in clinical trials, they provide limited details for safety data analysis. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…For example, harm outcomes are often accompanied with additional information such as the number of occurrences, severity, timing and duration that need to be taken into consideration. However, the predominant practice is to reduce this information to simple binary counts [4,19,[70][71][72]. We believe these challenges do not justify the prevalent use of simplistic analysis approaches for AE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, harm outcomes are often accompanied with additional information such as the number of occurrences, severity, timing and duration that need to be taken into consideration. However, the predominant practice is to reduce this information to simple binary counts [4,19,[70][71][72]. We believe these challenges do not justify the prevalent use of simplistic analysis approaches for AE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 4 14 15 It has also been argued that such guidelines do not go far enough and fail to account for the complex nature of harm outcomes data. 5 Tutorial papers or case studies detailing examples of appropriate analysis could lead to wider adoption of such recommendations and to improvements in analysis practices, and development of such resources was highlighted as a priority by workshop participants. While the acquirement of the necessary knowledge and skills to implement new methods is essential, so too is increasing awareness of good practices and alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…Open access data are not being analysed to its full potential. [1][2][3][4][5] Most notable inadequacies include ignoring information on repeated events and dichotomising continuous clinical and laboratory outcomes, with binary counts often presented using simple tabulations, indicating whether an event did or did not occur. Little formal analysis is performed but a comprehensive methods review undertaken by the authors revealed that there have been many published statistical methods proposed specifically to analyse adverse event data for both the interim and the final analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the predominant practice is to reduce this information to simple binary counts. [4,19,[70][71][72] We believe these challenges do not justify the prevalent use of simplistic analysis approaches for AE analysis.…”
Section: Discussionmentioning
confidence: 99%